Grapheme-Phoneme Learning in an Unknown Orthography: A Study in Typical Reading and Dyslexic Children - Law, Jeremy M.; De Vos, Astrid; Vanderauwera, Jolijn; Wouters, Jan; Ghesquière, Pol; Vandermosten, Maaike (Frontiers in Psychology, 2018)
In this study, we examined the learning of new grapheme-phoneme correspondences in individuals with and without dyslexia. Additionally, we investigated the relation between grapheme-phoneme learning and measures of phonological awareness, orthographic knowledge and rapid automatized naming, with a focus on the unique joint variance of grapheme-phoneme learning to word and non-word reading achievement. Training of grapheme-phoneme associations consisted of a 20-min training program in which eight novel letters (Hebrew) needed to be paired with speech sounds taken from the participant's native language (Dutch). Eighty-four third grade students, of whom 20 were diagnosed with dyslexia, participated in the training and testing. Our results indicate a reduced ability of dyslexic readers in applying newly learned grapheme-phoneme correspondences while reading words which consist of these novel letters. However, we did not observe a significant independent contribution of grapheme-phoneme learning to reading outcomes. Alternatively, results from the regression analysis indicate that failure to read may be due to differences in phonological and/or orthographic knowledge but not to differences in the grapheme-phoneme-conversion process itself.